PERLINDUNGAN HUKUM TERHADAP KARYAWAN YANG DIPAKSA PERUSAHAAN UNTUK MENGUNDURKAN DIRI AKIBAT PANDEMI COVID-19 - Mirah Delima Permata, (2021)
Termination of employment that occurs unilaterally often creates legal problems, one of which is the termination of employment due to the COVID-19 pandemic. The problem in this study, companies that terminate employment by forcing employees to sign resignation letters, and companies do not provide severance pay or compensation pay. This type of research is empirical research. The source of data collected as the main focus is primary data. Based on the research results, it can be concluded that there is no written protection for workers. If a case like this occurs, it can be solved by bipartite. If the bipartite fails, it can be continued with tripartite. And with the resignation letter, the letter is considered valid, as long as it cannot be proven. However, if you refer to the valid terms of the agreement, the letter can be canceled. It is hoped that there will be regulations governing legal protection for workers who are forced to sign resignation letters. The Manpower Office must create a work unit that is specialized in examining and investigating cases like this. And the public must be more critical and careful in carrying out orders from the company, by seeking legal consequences through the Act, so that adverse things do not occur.